Identifying Structural Suitability Components of Aged-friendly Mosques in Iran: A Qualitative Study - Samaneh Pourhadi; Aram Tirgar; Mandana Kalantar (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: One way to improve the social participation of the elderly is to pay attention to environmental adaptation, and ensure safety and independence of them in places they use. Due to the rapid growth of the aging population in Iran and considering the important role of mosques as one of the main religious-spiritual places for the elderly, conducting studies to determine the structural suitability components of the mosques in terms of geriatrics and ergonomics are necessary. Therefore, the present study aims to identify the structural suitability components of elderly-friendly mosques in Iran. Methods & Materials: This is a qualitative study using the content analysis method conducted in 2020. Participants were 18 eligible older adults (13 women and 5 men) aged 61-72 years (Mean±SD age=66.33±2.99) attended the mosques of Babol city who had the ability to communicate effectively and the willingness to participate in the study. The mosques were selected based on the geographical distribution (in north, south, east, and west). The data collection method was in-depth and semi-structured interviews, which continued until data saturation. Each interview was transcribed and analyzed step by step according to Kvale's method. Results: The extracted data were divided into 5 main categories and 18 subcategories as the structural suitability components of elderly-friendly mosques. Extracted main categories included: Outdoor Environment, Indoor Environment, Equipment, Basic Welfare Amenities, and Internal Facilities. Conclusion: The identified components can help find and prioritize the needs and select the type of interventions to be conducted in the mosque according to the characteristics of the elderly.